Milk Production in Kerala Trends and Prospects - K Narayanan Nair (ECONOMIC AND POLITICAL WEEKLY, 1979)
As part of the national strategy for augmenting milk production, cross-breeding and upgrading of milch cattle has been taking place in Kerala during the lust two decades. The programme moving at a slow pace in the 1950s and the 1960s, has been accelerated in the 1970s, and much effort has gone to improve the coverage and efficiency of the programme, This paper attempts to examine the contribution of animal husbandry and dairy development programmes to the increase of milk production in Kerala. Its chief findings are: (1) that there has been a considerable increase in the productivity of milch animals and total milk production in Kerala; (2) that the profitability of milk production has gone up over the years; and (3) that milk production in Kerala is mainly undertaken by small and marginal fanners. The paper also makes some broad projections of the demand for milk and milk products by 1990 and concludes that a mere programme of improved cross-breeding cannot possibly meet the projected demands. The paper briefly touches upon the recent demands for a ban on the slaughter of cows in Kerala Sid argues that there is no economic rationale behind such a demand. Any ban on the slaughter of cows in the state would be totally harmful to the growth of the livestock economy; and would surety affect adversely several development projects already undertaken.